2003
DOI: 10.1128/jvi.77.2.1163-1174.2003
|View full text |Cite
|
Sign up to set email alerts
|

Control of Viremia and Prevention of Simian-Human Immunodeficiency Virus-Induced Disease in Rhesus Macaques Immunized with Recombinant Vaccinia Viruses plus Inactivated Simian Immunodeficiency Virus and Human Immunodeficiency Virus Type 1 Particles

Abstract: Prophylactic vaccines that prevent diseases caused by viral pathogens typically elicit neutralizing antibodies (Abs), which rapidly clear virus, and/or cellular immune responses, which eliminate virus-producing cells. In a well-studied prototypical mouse retroviral system, both arms of the immune system are needed to control Friend murine leukemia virus-induced viremia and/or splenomegaly and to prevent the transition to a persistent infection status that invariably leads to erythroleukemia and death (35). Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 86 publications
3
28
0
Order By: Relevance
“…Long-term control of X4-tropic pathogenic SHIV has been reported in follow-up studies of several pre-clinical AIDS vaccine trials (Willey et al, 2003;Sadagopal et al, 2005). Whilst these vaccine regimens utilized Env as an immunogen (Amara et al, 2002), we have developed vaccine…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term control of X4-tropic pathogenic SHIV has been reported in follow-up studies of several pre-clinical AIDS vaccine trials (Willey et al, 2003;Sadagopal et al, 2005). Whilst these vaccine regimens utilized Env as an immunogen (Amara et al, 2002), we have developed vaccine…”
Section: Discussionmentioning
confidence: 99%
“…In a model of X4-tropic simian/human immunodeficiency virus (SHIV) 89.6P or 89.6PD infection (Reimann et al, 1996;Lu et al, 1998), which causes rapid CD4 + T-cell depletion leading to an acute crash of the host immune system in macaques, several pre-clinical trials of prophylactic AIDS vaccines have successfully shown that efficient CTL induction results in control of virus replication and prevention of acute AIDS progression (Barouch et al, 2000;Amara et al, 2001;Matano et al, 2001;Rose et al, 2001;Shiver et al, 2002;Willey et al, 2003 We have developed a prophylactic AIDS vaccine using a DNA-prime/Gag-expressing Sendai virus (SeV-Gag) vector boost system and have shown its potential for efficient induction of Gag-specific CTL responses in Burmese rhesus macaques (Kano et al, 2002;Matano et al, 2004). In preclinical trials in an acute AIDS model, all of the macaques vaccinated with the DNA-prime/SeV-Gag vector boost system controlled SHIV89.6PD replication after challenge (Matano et al, 2001;Takeda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they bear the HIV type 1 (HIV-1) envelope glycoprotein, SHIVs have been valuable for assessing vaccine-induced anti-HIV-1 neutralizing antibodies (2,3,5,18,24). Furthermore, highly pathogenic SHIVs induce an unusually rapid, complete, and irreversible depletion of CD4 ϩ T lymphocytes in rhesus monkeys, thereby providing a readily demonstrable endpoint in vaccine experiments.…”
mentioning
confidence: 99%
“…In preliminary experiments to generate molecular clones of highly pathogenic SHIV DH12R (11), DNA was prepared from rhesus monkey peripheral blood mononuclear cells (PBMC), infected with the SHIV DH12R-PS1 derivative (24), and subjected to digestion by several restriction enzymes. Southern blot hybridization analyses revealed that EcoRI converted the circular forms of viral DNA into linear molecules approximately 10 kbp in size, consistent with the presence of a single EcoRI site within unintegrated SHIV DH12R DNA (data not shown).…”
mentioning
confidence: 99%